2015
DOI: 10.1007/s11999-015-4224-y
|View full text |Cite
|
Sign up to set email alerts
|

Which Surgical Treatment for Open Tibial Shaft Fractures Results in the Fewest Reoperations? A Network Meta-analysis

Abstract: Background Open tibial shaft fractures are one of the most devastating orthopaedic injuries. Surgical treatment options include reamed or unreamed nailing, plating, Ender nails, Ilizarov fixation, and external fixation. Using a network meta-analysis allows comparison and facilitates pooling of a diverse population of randomized trials across these approaches in ways that a traditional meta-analysis does not. Questions/purposes Our aim was to perform a network meta-analysis using evidence from randomized trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 42 publications
3
86
1
6
Order By: Relevance
“…In the open tibial shaft management NMA by Foote et al [7], only two pairwise comparisons included a sufficient number of studies for a meaningful assessment of heterogeneity. An initial visual assessment of the forest plots comparing unreamed nailing with external fixation (Fig.…”
Section: Are the Results Of Individual Studies In The Direct Comparismentioning
confidence: 99%
See 2 more Smart Citations
“…In the open tibial shaft management NMA by Foote et al [7], only two pairwise comparisons included a sufficient number of studies for a meaningful assessment of heterogeneity. An initial visual assessment of the forest plots comparing unreamed nailing with external fixation (Fig.…”
Section: Are the Results Of Individual Studies In The Direct Comparismentioning
confidence: 99%
“…Returning to the NMA of open tibial shaft fracture management by Foote et al [7] in the case scenario presented in Part I of the Users' Guide for Surgeons, we saw that the NMA had restricted eligibility to RCTs and quasirandomized trials and that the authors reported the risk of bias for each article. More to the point, the article also presented the risk of bias associated with the body of evidence addressing each treatment effect estimate.…”
Section: Evaluating Certainty In Estimates Of Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside these User's Guides, we also present a well-performed network meta-analysis on the care of a common fracture [7]. We hope that readers will take advantage of this opportunity to try something new, and to learn.…”
Section: S S Leopold MD (And) Clinical Orthopaedics and Relatedmentioning
confidence: 99%
“…If you are familiar with network meta-analyses, I am confident you will enjoy the paper by Foote et al [7] on tibial fractures in this issue of CORR 1 . But if this study design is new to you, I hope you will take advantage of this opportunity to learn how to read and enjoy network meta-analyses by taking advantage of the User's Guides [2,6].…”
Section: S S Leopold MD (And) Clinical Orthopaedics and Relatedmentioning
confidence: 99%